Essay as a Form of Final Control (Exam) for Master’s Degree Students - Nesyna, Svetlana Vadimovna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The important goal of Russian universities is development of Master's Degree Programs. It requires profound changes in educational content and methods. This work presents the experience in approbation of essay as a form of exam in education of 20 students of Master Program "Preschool education". In our study we suppose that using the essay helps to reduce negative effects of traditional forms of control and activates self-development of participants. The incomplete sentences technique as a data-gathering tool was applied after the exam. According to the results, creation of essay contributes to generalization and understanding, comprehension of the problem information, makes cognitive and metacognitive processes more active. Such form of final control gives psychological comfort, creates a situation of success. It strengthens needs for autonomy, competence, relatedness, which are sources of internal motivation as the basis of subjectness and self-development tendency.